"RUNNING DISCUSSION " AS A STRATEGY TO CREATE A FUN ENGLISH LESSON - Verastuty Verastuty (English Language Teaching and Research, 2018)
Using a right strategy for our class is an important thing. Eventhough there are so many strategies that we can use in our class, still we have to think the best and suitable one for the class. We need to consider about the learning materials, students’ learning behaviours, classroom or school condition, students’ ability and others, so that the students can learn maximally.SMAN 14 Padang has nine classes for grade ten. They are five classes for science program and 4 classes for social classes. Each class has heterogent students’ learning behaviour, but most of them are kinesthetic learners with low to middle English ability. Since most of them are kinesthetic learners, it is important to choose a strategy which can accomodate the majority learners’ type but do not left the others. One of the strategy is “Running Discussion” strategy. In fact, this strategy is a modified strategy from “Running Dictation” strategy. It is modified to make it suitable for the students condition.The result shows that all of the classes from five classes for science programme and 4 classes for social classes programme were enjoy and happy during the class.Keywords: English learning, heterogent learners’ type, Kinestetics learners, Running discussion